(untitled) (Fiep Bulletin - online, 2019)
This work aims to perform a microbiological analysis of places and objects used in places where physical activitypractices such as schools, academies and squares occur and suggest procedures for asepsis and prophylaxis against thesecontaminants in favor of society. Samples will be collected following the Standard Operational Procedure - POP / Microbiology.The city will be divided into 5 (five) macro regions. The collection sites will be selected geographically divided into five regions:North, South, East, West and Center, in order to obtain a reliable profile of the reality of the capital João Pessoa of the state ofParaíba, having a collection in a public place (square) and one private (academy) and one (public or private) school for eachregion totaling 15 (fifteen) collection sites in several areas of each one that will be identified in the presentation of the results andat the time of collection and presented in attached letters of agreement . All work will be governed by CNS Resolution 466/12dealing with scientific research. Bacillus ssp, Esherichia coli, Enterobacter spp., Bacillus spp., Bacillus ssp, Escherichia coli,Enterobacter spp., Bacillus spp. Staphylococcus coagulase negative and Klebsiella spp, these microorganisms have a widevariety of species and are quite resistant to adverse conditions, are widely distributed throughout the world but cause greaterconcern in developing countries due to issues such as infrastructure, basic sanitation and other factors which makes it difficult tocombat or prevent these agents, which can pose a huge risk to health.